Performance Analysis of The Last Significant Bit (LSB) Method in Steganography for Data Hiding in Image Data - Baso, Fadhlirrahman (PT. Lontara Digitech Indonesia, 2023)
Technology as a means of conveying information can have significant implications for the security and confidentiality of data and information content. When a sender wishes to convey a message to someone and does not want the message to be easily visible, the concealment of this message becomes crucial for the sender. One commonly used method for data concealment is the Least Significant Bit (LSB) method in steganography. The LSB method is preferred for its simplicity, fast process, and greater capacity. Messages are embedded by replacing the least significant bit in the host image with the message bits, with the rule that the number of message bits does not exceed the number of bits in the host image. Based on research findings, the results of steganography are difficult to distinguish from the original content through visual observation. Therefore, it can be concluded that the steganography method is highly effective for concealing a message.